The memory keeper's daughter. - Edwards, K. (New York Penguin books, 2005)
"When a woman is caught in the middle of a snowstorm and goes into labor, her husband must help deliver twins with the aid of a nurse. When the baby girl is born with Downs Syndrome, the husband decides to send the baby to a mental institution with the nurse; and tell his wife it died. For the next 25 years, the secret destroys the marriage and tears the family apart. The son who lived must deal with his parents' troubled relationship while he also yearns for the sister he never knew. Meanwhile, the nurse decided to raise the baby herself, and is struggling to make ends meet as a single mother to a disabled child"--Copyright description.
Copyright Claimant: Sony Pictures Television Inc. Date of Creation: 2008; Date of Publication: 2008-04-12; Registration Number / Date: PA0001608883 / 2008-06-16.
Sources used: videocassette container; Copyright catalog online; Copyright description.
Keywords: Novel--fiction